Appraisal of the Flooding Behaviour of Rotating Packed Beds - Garba, Usman; ROUZINEAU, David; Meyer, Michel (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Rotating packed beds (RPBs) enhances mass transfer processes because a centrifugal force which is several -times greater than gravity is used as the driving force. The complexity of fluid flow across RPBs has made predicting and accurately determining their hydrodynamic behaviours difficult. The flooding point as a hydrodynamic characteristic is essential for the accurate design and scale-up of RPBs. However, variations in flooding point definitions and methodologies across the literature highlight the need for standardized approaches in studying RPB flooding phenomena. This study compared four approaches based on pressure drop fluctuations and the volume of liquid ejected from the RPB to determine the onset of flooding in RPBs using experimental results from a pilot-scale counter-current RPB. For rotational speeds of 300 -1500 rpm, gas flow rate of 100-300 Nm3/h, and liquid flow rates of 0.39-0.75 m3/h, the pressure drop varied from 314 to 2,100 Pa. Quantitative comparisons of the results based on different flooding point definitions showed wide variations with the values of the pressure drop at the onset of flooding differing by as much as 325 %. A quantitative approach based on virtual observations and the ejection of 8 % of the total liquid flow rate from the rotor’s eye is proposed as the standard method for identifying the onset of flooding in RPBs.